Pregnancy does not influence colonic polyp multiplicity but may modulate upper gastrointestinal disease in patients with FAP. Issue 8 (11th May 2007) - Suraweera, Nirosha; Latchford, Andrew; McCart, Amy; Rogers, Pauline; Spain, Sarah; Sieber, Oliver; Phillips, Robin; Tomlinson, Ian; Silver, Andrew
Abstract : Background: Reproductive factors have been shown by epidemiology studies to alter colorectal cancer risk in women. Familial adenomatous polyposis (FAP) patients carry a germline adenomatous polyposis coli (APC) mutation predisposing to multiple adenoma formation in the intestine. The Min mouse provides a good model of FAP, and we recently reported a significant increase in intestinal tumour multiplicity in a recombinant line of mice following pregnancy. Aim: We considered whether reproduction modulates intestinal tract disease in a large cohort of female patients with FAP (n = 180). Results: Multiple regression analysis showed that the number of colonic polyps observed was not related to the person's pregnancy status nor the position of their APC germline mutation. The proportion of women attaining a high Spigelman stage (3 or 4) was unrelated to having a pregnancy prior to attaining the maximum Spigelman stage (p = 0.6). On the other hand, having a pregnancy significantly increased the proportion of women that attained the highest Spigelman stage when their APC germline mutation occurred within the mutation cluster region or at or after codon 1020 (50%, 6/12, p = 0.005 and 42%, 13/31, p = 0.006, respectively; multivariable logistic regression). Conclusion: Our data suggest that reproduction may influence disease severity in the upper gastrointestinal tract in patients with FAP.